Geopolitics of Sensing and Knowing: On (De)Coloniality, Border Thinking, and Epistemic Disobedience - Mignolo, Walter (Journal of Research in Humanities, 2023)
Epistemic disobedience and border doing/thinking requires to shift the geography of knowing, sensing and understanding. The shift means to start from what the vocabulary (in the disciplines as well as in every day life) that the rhetoric of Western modernity silenced, disavowed, distorted and in the best cases reduced and integrated to the regional and limited semantic of Western vocabulary derived mainly from Greek and Latin. When languages other than Greek and Latin (like Arabic for instance), entered Western vocabulary they entered in "disguise" and it require philological investigation to realize that certain words comes from Arabic or other languages with which Europeans intervened. Pluriversality is the horizon that epistemic disobedience and border doing and thinking are aiming at. And since both border doing/thinking presupposes delinking from territorial epistemology, and territorial epistemology is modern/colonial, both enact decoloniality; which means delinking from modernity/colonialty (short hand for Colonial Matrix of Power, CMP) and re-existing on other grounds that for the moment are planetary borderlands.